Development of irrigation scheduling at the whole farm level - Ismanov, Mukammadzakhrab, author; Espinoza, Leo, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2012)
The average cotton farmer in the Mid-South works with large numbers of fields. Different crops, soil types, and planting times complicate irrigation scheduling at the whole farm level. This is probably the main reason why many farmers still do not use the irrigation scheduling tools. Results of irrigation scheduling in different counties in Arkansas during the last five years show that a developed potential evapotranspiration (PET)-based irrigation scheduler is an effective at the whole farm level. Main tools of this method are evapotranspiration (ET) and rain gauges. Comparison different ET tools shows that the atmometer is better suited to farm irrigation scheduling purposes in terms of price, accuracy of data, easy installation, and monitoring. PET data of different atmometers installed in the same place may differ by 1.69 % from the average PET during a three-month period. Evaluating a water deficit level of the particular field is very important. Soil type, tillage system and field configuration may affect the water deficit level of the field. The field water deficit method helps to evaluate the soil moisture level between irrigation or rainfall intervals and to determine the next irrigation time.
Irrigated agriculture responds to water use challenges
Irrigation scheduling at the whole farm level
Presented at Irrigated agriculture responds to water use challenges - strategies for success: USCID water management conference held on April 3-6, 2012 in Austin, Texas.